2009
DOI: 10.1186/1756-0500-2-232
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Tympanic Membrane perforation: An aetiological profile

Abstract: BackgroundTraumatic perforation of the tympanic membrane may be due to direct or indirect source. The aim of the study is to profile the various aetiologies of traumatic tympanic membrane perforation in Ilorin, north central Nigeria.A retrospective review of 64 patients seen at the University of Ilorin Teaching hospital, Ilorin, Nigeria over a ten year period (January 1998 to Dec 2007) with history of traumatic tympanic membrane perforation from various causes, these also included multiply injured patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
29
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 3 publications
11
29
0
4
Order By: Relevance
“…Other reports had age ranges of 29.2 to 33.6 years. 15,16,17 The male preponderance found in our study resonates with that reported in a study in Ilorin, North-central Nigeria. 15 This may be due to more outdoor activities in males than the females.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other reports had age ranges of 29.2 to 33.6 years. 15,16,17 The male preponderance found in our study resonates with that reported in a study in Ilorin, North-central Nigeria. 15 This may be due to more outdoor activities in males than the females.…”
Section: Discussionsupporting
confidence: 91%
“…Exploration of the causes and mechanisms of TTMP revealed a trend similar to those reported from other studies. 15,18 Assault (altogether 50.9%) was a common and prominent cause of TTMP in this study like in other previous reports (37.4-86.4%). 16,19,20 Assaults ranged from domestic attacks like slaps from spouse and armed bandits, to injuries inflicted by state security personnel.…”
Section: Discussionsupporting
confidence: 88%
“…[11][12][13] The presenting symptoms of traumatic TMP and their frequency were hearing loss (95.3%), bleeding (68.8%), CSF leak (15.6%), dizziness (9.4%), tinnitus (52%), infection (37.5%), and pain (59.4%). [5] Both our patients had ear pruritus. One patient had eczematous external otitis and the other suffered from AR.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In another retrospective analysis of 198 patients with traumatic TMP, the causes and frequencies of the traumatic TMPs were as follows blow (n=90), collision (n=40), insertion of cotton bud (n=36), insertion of sharp object (n=9), firecracker explosion (n=5), barotrauma (n=4), kick by a child (n=2), weld bead (n=2), and unknown (n=10) and 45.5%, 20.2%, 18.1%, 4.5%, 2.5%, 2%, 1%, 1%, and 5% respectively. [6] Overpressure is the most common mechanism of trauma to the TM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation